Mapping causal mutations by exome sequencing in a wheat TILLING population: a tall mutant case study - Mo, Youngjun (2018)
Forward genetic screens of induced mutant plant populations are powerful tools to identify genes underlying phenotypes of interest. Using traditional techniques, mapping causative mutations from forward screens is a lengthy, multi-step process, requiring the identification of a broad genetic region followed by candidate gene sequencing to characterize the causal variant. Mapping by whole genome sequencing accelerates the identification of causal mutations by simultaneously defining a mapping region and providing information on the induced genetic variants. In wheat, although the availability of a high-quality draft genome assembly facilitates mapping and mutation calling, whole genome resequencing remains prohibitively expensive due to its large genome. In the current study, we used exome sequencing as a complexity reduction strategy to detect mutations associated with a target phenotype. In a segregating wheat EMS population, we identified a clear peak region on chromosome arm 4BS associated with increased plant height. Although none of the significant SNPs seemed causative for the mutant phenotype, they were sufficient to identify a linked ~ 1.9 Mb deletion encompassing nine genes. These genes included Rht-B1, which is known to have a strong effect on plant height and is a strong candidate for the observed phenotype. We performed simulation experiments to determine the impacts of sequencing depth and bulk size and discuss the importance of considering each factor when designing mapping-by-sequencing experiments in wheat. This approach can accelerate the identification of candidate causal point mutations or linked deletions underlying important phenotypes.